Mechanism of oolongtheanin formation via three intermediates. Issue 11 (12th March 2020) - Hirose, Sayumi; Kamatari, Yuji O.; Yanase, Emiko
Graphical abstract: Highlights: A novel intermediate was found in the formation of oolongtheanins from catechins. A mechanism of oolongtheanin formation was then proposed. This mechanism was confirmed by GC–MS and 1 H NMR experiments. Abstract: To clarify the mechanism of oolongtheanin formation, the oxidations of (−)-epigallocatechin and (−)-epigallocatechin gallate were investigated, and key intermediates were isolated. These intermediates were determined to be dehydrotheasinensins and pro-oolongtheanins, which we have reported previously, and one novel intermediate. Based on the chemical structures of these intermediates, a mechanism was proposed for oolongtheanin formation from catechins, and confirmed by NMR and GC–MS analysis.